A comparative study of some commercially available tests for rheumatoid factor. Issue 5 (May 1974) - MacSween, R. N. M.; Hughes, Hazel; Breen, Catriona; Kitchen, P.; Cathcart, Brenda; Buchanan, W. W.
Abstract : Seven commercially available screening tests for rheumatoid factor and two quantitative tests have been compared with the standard Rose-Waaler test in a series of 477 sera from patients with various joint diseases. Markedly different results were obtained, and on the basis of our findings suggestions are made as to what we consider to be the most satisfactory currently available tests.